The Great Wall through time : a 2,700-year journey along the world's greatest wall - Du, Fei (Illustrator); DK Publishing, Inc. (New York, NY : DK Publishing, 2022)
Panoramic illustrations and fascinating text reveal the story of the Great Wall and the individuals who helped build it, bringing to life key periods and turning points in the Great Wall's history.
The story of the Great Wall, map of the Great Wall -- The first long wall, Nanyang, 656 BCE -- A single barrier, inner Mongolia, 210 BCE -- SIege at Mount Baideng, Pingcheng, 200 BCE -- Military games, inner Mongolia, 99 BCE -- Return of a hero, Kucha, 644 CE -- The barrier in the grasslands, Heilongjiang, 1138 CE -- The Ming Great Wall, Juyong Pass/Gubeikou, 1571 CE -- The "Horse-Tea" Market, Yulin, 1610 CE -- Defending the bridge, Jiumenkou Pass, 1644 CE -- The Battle of Shanghai Pass, SHangaiguan, 1644 CE -- The greatest pass under heaven, Jiayu Pass, 1880 CE -- The Beijing to Paris rally, Huailai, 1907 CE -- The Great Wall today, Yanmen Pass, 2022 CE -- The Great Wall through the ages time-travelinq quiz -- Glossary.
Keywords: JUVENILE NONFICTION / History / Asia; JUVENILE NONFICTION / Architecture; JUVENILE NONFICTION / History / Ancient; Great Wall of China (China) -- Juvenile literature; Great Wall of China (China) -- History -- Juvenile literature; China -- History -- Juvenile literature; China; China -- Great Wall of China; illustrated books; History; Illustrated works; Juvenile works; Illustrated works; Ouvrages illustrés.